The View of Islam on Religion Radicalization on Child Violence - Atiek Noer Chalimah (International Conference of ASEAN Prespective and Policy (ICAP), 2018)
Recently, the teaching of jihad in Islam has often been the target of allegations as the main source of violence in the name of religion. One is the case of child abuse. Radicalism in the language means to stand in extreme positions and away from the middle position or beyond the limits of reasonableness. So the idea of religious radicalization that is considered closely linked to the practice of child abuse. In efforts to deradicalize religion in child violence and deradicalization of Islamic thought through education, it is only natural that the national commitment is demonstrated through boarding school. Also, it is necessary to deradicalization of Tafseer; this is an attempt to break the paradigmatic chain that led to the construction of a radical interpretation. Religion does not teach its people to commit child abuse. Religion also teaches people to love one another and give more attention; do not choose to commit violence.